2007
DOI: 10.1258/096914107782066220
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of faecal occult blood tests used in screening for colorectal cancer: a systematic review

Abstract: Objective To determine the accuracy of guaiac and immunochemical faecal occult blood tests (FOBTs) for the detection of colorectal cancer in an average-risk screening population. Methods Fifteen electronic databases, the internet, key journals and reference lists of included studies were searched. We included diagnostic accuracy studies that compared guaiac or immunochemical FOBTs with any reference standard, for the detection of colorectal cancer in an average-risk adult population, with sufficient data to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 74 publications
8
101
0
10
Order By: Relevance
“…However, colorectal cancer can be prevented, or treated effectively if detected early, through screening (3). Evidence indicates efficacy of screening in reducing cancer mortality and, in some instances, incidence (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, colorectal cancer can be prevented, or treated effectively if detected early, through screening (3). Evidence indicates efficacy of screening in reducing cancer mortality and, in some instances, incidence (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Other review articles have also reported a wide range of sensitivities. [7][8][9][10][11] The lack of a precise estimate of sensitivity has resulted in confusion among clinicians when applying FOBT for colorectal cancer screening. One reason for the wide range of sensitivities may relate to verification bias (also known as work-up bias).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, before performing gFOBTs, patients should avoid the drugs mentioned above and should follow a proper diet. The sensitivity and specificity for gFOBTs is 25-38% and 74%, respectively (24). However, these tests are currently no longer considered important, and their routine use has been discontinued.…”
Section: Discussionmentioning
confidence: 99%